Determining the Point of B-Cell Differentiation in the Bursa of Broiler Chicken Embryos with Phenotype Analysis - Pharr, Gregory T.; Wang, Hui; Elliott, Katie E.C.; Evans, Jeff D. (International Journal of Poultry Science, 2025)
Background and Objective: A major B-cell differentiation event has been reported to occur in the bursa between Embryonic Days (ED) 15-19 and is detected by the upregulation in expression of a Lewis×(Lex) carbohydrate on developing B-cells using monoclonal antibodies. The goal of this project was to determine the onset of Lex expression in bursal B-cells in the Ross 708 broiler line. Materials and Methods: Frozen sections of pooled bursas were prepared from ED15 and ED19 and were evaluated by immunohistochemistry (IHC) using the anti-Lex and anti-chB6 antibodies. Results: In the embryonic bursa, very low levels of Lex expression was detected by ED15. However, the intensity of Lex expression increased markedly at ED19 and co-localized with a B-cell- specific marker in the developing bursal follicles. Conclusion: We conclude that repertoire development initiates between ED15 and ED19 in the embryonic bursa of the Ross 708 line, as has been shown in White Leghorn embryos in studies by others. This information is important for planning future B-cell development studies in this broiler line.